Delayed acquisition of airway commensals in antibiotic naïve children and its relationship with wheezing in rural Ecuador - Cardenas, Paul A.; Cox, Michael J.; Willis-Owen, Saffron A.; Moffatt, Miriam F.; Cookson, William O.; Cooper, Philip J. (Frontiers in Allergy, 2023)
The hygiene hypothesis identified a relationship between living in rural areas and acquiring protective environmental factors against the development of asthma and atopy. We have previously studied infants living in the rural tropics of Ecuador who were corticosteroid-naïve with limited antibiotic exposure, finding a correlation between particular bacterial species and early onset wheezing(1). We now describe a longitudinal study of infants conducted to determine how the microbiome and its relationships with wheezing vary with age.Methods: Sequencing of amplicons of the bacterial 16S rRNA gene was performed from oropharyngeal samples from 110 infants with a history of recurrent episodic wheezing sampled at different ages (7, 12, and 24 months) and compared to the sequencing of oropharyngeal samples from 150 healthy infants sampled at the same time points. Bioinformatic analyses were conducted using QIIME and R.Results: As expected, the microbiota diversity consistently increased as the infants grew older. Considering age-based microbiota changes, infants with wheeze had significantly lower species richness than healthy infants at 7 months but not at 12 or 24 months. The majority of core and accessory organisms increased in abundance and prevalence with age, with a small number declining. At 7 months, a single Streptococcus OTU and member of the core microbiota was characteristically increased in infants with wheeze compared to controls.In a cohort with limited antibiotic and corticosteroid use, a progressively more complex and diverse respiratory microbial community develops with age. The respiratory microbiota in early life is altered in infants with wheeze compared to controls, but this does not persist in older infants.